Ergonomics in violin and piano playing: A systematic review. (October 2020) - Chi, Ju-Yang; Halaki, Mark; Ackermann, Bronwen J.
Abstract: This systematic review aimed to evaluate whether muscle activity and playing-related musculoskeletal disorders are associated with musicians' anthropometrics and their instrument size or set-up during violin and piano performance. Studies were retrieved systematically from six databases on 1 April 2019 combined with hand searching results. The Appraisal tool for Cross-Sectional Studies (AXIS tool) was used to evaluate the methodological quality of the included papers. A total of twenty articles were identified. Most included studies focussed on either the adjustment of the shoulder rest in violinists, or the hand size in pianists. However, methodological quality was inconsistent. The electromyography data reported by the included studies were not appropriately processed and interpreted. Studies generally reported the use of a shoulder rest changes muscle activity and smaller hand size is correlated to increased playing-related musculoskeletal disorders incidence. However, no conclusions can be drawn due to heterogeneity and low quality of methodology in the available literature.